Effect of natural gas components on its flame temperature, equilibrium combustion products and thermodynamic properties - Kayadelen, Hasan Kayhan (ELSEVIER SCI LTD, 2017)
It is a known fact that the composition of natural gas varies widely from source to source and from time to time even in the same source. Such variations in gas composition cause variations in flame temperature, its combustion products and thermodynamic properties which can affect gas-fueled engine performance and its emissions. The purpose of this study is to investigate effects of varying amounts of natural gas diluent components such as ethane (C2H6), isobutane (C4H10), propane (C3H8), carbon dioxide (CO2) and nitrogen (N-2) on methane air combustion under different pressures, unburned mixture temperatures and equivalence ratios. Results show that adiabatic flame temperature is mostly increased by isobutane followed by propane and ethane however it is mostly influenced by CO2 content in the gas which decreases flame temperature 80 K in %70 CH4 - %30 CO2 mixture at stoichiometric conditions. As for specific heat, the highest increase is again for isobutane followed by propane and ethane content but it is decreased mostly by N-2. Effect of increasing secondary fuel content on product species is greatest at equivalence ratio near unity except for CO and H-2. Analysis results including equilibrium compositions are validated and expected to be a reference guide for scientists, engineers and NG consumers to evaluate and compare natural gas samples of different compositions. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Natural gas; Methane; Gas quality; Pipeline quality; Flue gas analysis; EMISSION CHARACTERISTICS; DIESEL-ENGINE; FUEL; PERFORMANCE; PREDICTION; DILUENTS; Energy & Fuels; Engineering